Analysis of Islamic Banking Performance in West Nusa Tenggara Post Global Financial Crisis 2008-2009: Error Correction Model Approach - Aprizal, Anggi; Basuki, Agus Tri; Wiranatakusuma, Dimas Bagus (Journal of Islamic Economic and Business Research, 2025)
Islamic Banking has an important role in supporting economic growth and financial stability. The positive development of Islamic Banking in West Nusa Tenggara (NTB) is a strategic concern, considering that studies at the provincial level are still limited, especially regarding the influence of internal and external factors. This study analyzes the performance of Islamic Banking in NTB during 2010-2023 using Return on Assets (ROA) as an indicator of profitability, with the Error Correction Model (ECM) method to measure short-term and long-term relationships. Internal factors include Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), Bank Size (BS), and Third Party Funds (TPF). External factors include Gross Regional Domestic Product (GDRP), inflation (INF), exchange rate (ER), and Islamic Stock Index (ISS). The study results show that internally, FDR has a significant negative effect in the long term, reflecting liquidity risk. NPF has a negative impact in the short term but a positive impact in the long term, indicating optimal risk management. BS shows operational inefficiency, while DPK has a significant positive effect in the short term but a negative effect in the long term. Externally, GRDP supports profitability in the short and long term. Inflation has a significant negative impact, the exchange rate has a significant positive impact in the long term, and ISS has a significant positive impact in the long term. This study emphasizes the importance of increasing liquidity efficiency and financing risk management by Islamic banking. The government and regulators also need to maintain economic stability through controlling inflation and the exchange rate to support the performance of this sector.